Student Scientific Literacy Skills of Competence Aspect in Human Reproductive System Material - Damayanti, Alfiya; Kuswandi, Paramita C (Jurnal Pedagogi dan Pembelajaran, 2024)
Technological developments facilitate teachers to develop strategies, methods, teaching materials to enhance students' 21st-century skills. However, not all schools have excellent facilities and teachers who can utilize these facilities to develop learning strategies that support these skills. This situation contrasts with the condition, most of which have good school facilities and teachers who can keep up with technological developments. Therefore, the purpose of this research is to analyze the attainment of scientific literacy skills in human reproductive system material among senior high school students and to investigate the differences in scientific literacy skills in human reproductive system material among schools as a result of school facility and teacher factors. The population for this research comprises class XI senior high school, with a sample of 189 students selected from six schools. This research is descriptive research using a survey method to describe the achievement of students' scientific literacy skills. The instruments used were questionnaires and multiple-choice tests. The collected data were analyzed using descriptive statistics and the Kruskal-Wallis test. The result indicates that the scientific literacy skills of senior high school student in Yogyakarta are good category and there are significant differences in the scientific literacy skills of each school as a result of the availability of school facilities. The conclusion of this research is that there are significant differences in the achievement of students' scientific literacy skills as a result of school facility factors.